AN ANALYSIS OF ENGLISH LOANWORD IN MALAY TELUK BUNTAL SUBDIALECT - Arita Destianingsih; Diah Paramita Sari; Ari Satria (INOVISH JOURNAL, 2019)
This study aimed to analyze and describe the types of English loanword in Teluk Buntal Malay sub-dialect. This was classified into descriptive research. The source of data was taken from the recorded dialogue which was interpreted into written data. The result of the study showed that there were 8 English loanwords that commonly used in daily conversation by the Malay people of Teluk Buntal. The type of English loanword discovered in this study encompassing loanword, loan blends and loan shift. Hence, all of the words found to be the most dominant type were loanwords and based on structure of English loanwords type, it was categorized into simple word in term of spelling and meaning.